Polarization noise induced by photon-phonon interaction in hollow-core photonic crystal fibres - Zhong, W.; Heim, B.; Elser, D.; Marquardt, Christoph; Leuchs, Gerd (2011 Conference on Lasers and Electro-Optics Europe and 12th European Quantum Electronics Conference, CLEO EUROPE/EQEC 2011, 2011)
Guided acoustic wave Brillouin scattering (GAWBS), a weak forward scattering that stems from the interaction of light with thermally excited transverse phonons, has been studied in both standard fibres [1] and photonic crystal fibres [2, 3]. The acoustic phonon vibrations modulate the stress distribution in the silica fibre core, thus modulating the refractive index and inducing polarization and phase noise in the light field. © 2011 IEEE.
CRIS-Team Scopus Importer:2022-06-05